Notes on the Fifteenth-Century Manuscript in the Advocates’ Library known as the Dupuy Book of Hours (MS. 18.7.18) - Dickson, W (Proceedings of the Society of Antiquaries of Scotland, 1916)
The manuscript is a Flemish Horaa or Book of Hours, written and illuminated in the latter part of the fifteenth century. It belonged for some generations to a French family named Dupuy. These are intended for the use of the laity in private devotion. This example contains the calendar, lessons from the Gospels, the two prayers to the Virgin, hours of Roman use, penitential psalms and litany, office of the dead and memorials of various saints. The main interest of the book is ten beautiful miniatures of various sacred subjects many of which are described and illustrated in detail.